2023
DOI: 10.1055/a-2009-1360
|View full text |Cite
|
Sign up to set email alerts
|

Behandlungsoutcome von Maßregelpatient:innen mit Migrationshintergrund. Analyse bayerischer Daten zur Qualitätserfassung von 2010 bis 2019

Abstract: Zusammenfassung Ziel der Studie Untersuchung des Zusammenhangs zwischen Migrationshintergrund von Patient:innen und dem erfolgreichen Abschluss der Maßregelbehandlung hinsichtlich Unterbringungsdauer und Entlassmodus Methodik Auf Basis der Ergebnisqualitätserfassung des bayerischen IFQM von 2010–2019 wurden mittels paarweiser Zuordnung Migrant:innen und Nicht-Migrant:innen verglichen, die hinsichtlich folgender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Men were more likely to have a negative treatment outcome in Franke et al (40) and Hartl (37); though no significant difference was observed in Berthold and Riedemann (17). Patients with a migration background were less likely to be successfully discharged from services (60). Berthold and Riedemann (17) found no link between age and treatment outcome.…”
Section: Social and Demographicmentioning
confidence: 99%
“…Men were more likely to have a negative treatment outcome in Franke et al (40) and Hartl (37); though no significant difference was observed in Berthold and Riedemann (17). Patients with a migration background were less likely to be successfully discharged from services (60). Berthold and Riedemann (17) found no link between age and treatment outcome.…”
Section: Social and Demographicmentioning
confidence: 99%